2015
DOI: 10.2135/cropsci2014.06.0450
|View full text |Cite
|
Sign up to set email alerts
|

Agro‐morphological Characterization of West and Central African Pearl Millet Accessions

Abstract: Pearl millet [Pennisetum glaucum (L.) R. Br.] was domesticated in Sahelian West Africa. This highly outcrossing crop is one of the most important staple cereals in the semiarid tropics, adapted to very harsh rain‐fed conditions. Agro‐morphological characterization of local germplasm is very important to better understand existing diversity, ease targeted genetic broadening of breeding populations, and potentially link this knowledge to genotypic information. The objectives of our study were to (i) characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 33 publications
6
51
1
1
Order By: Relevance
“…In the case of seedling vigour, the large G × L interaction can be explained by the differences in precipitation among the three locations. Kountche et al (2013) and Pucher et al (2015) also found high G × E interactions for reaction to downy mildew. The downy mildew pathogen is, like pearl millet, highly allogamous.…”
Section: Observed Patterns Of G × E Interactionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the case of seedling vigour, the large G × L interaction can be explained by the differences in precipitation among the three locations. Kountche et al (2013) and Pucher et al (2015) also found high G × E interactions for reaction to downy mildew. The downy mildew pathogen is, like pearl millet, highly allogamous.…”
Section: Observed Patterns Of G × E Interactionmentioning
confidence: 94%
“…The pathogen's virulence can match the resistance of the millet population in regions Table 2). F. T. Sattler et al 268 they occur together (depending on the history of the field), causing the high interaction variance (Pucher et al, 2015).…”
Section: Observed Patterns Of G × E Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity based on simple sequence repeat markers in the current West African pearl millet inbred germplasm association panel (WA-PMiGAP) is reported in detail by Stich et al (2010). According to Pucher et al 2015, flowering time is differentiated in pearl millet based on latitude with varieties toward the north being more earlier flowering compared with varieties preferred for the south. This could also be the reason why in the present study controlling for population structure and not so much of kinship was important for FLO.…”
Section: Low Level Of Differentiation Between P-levels In Field Evalumentioning
confidence: 99%
“…Having been domesticated in the Sahelian zone of West Africa (WA; Harlan et al 1976;Tostain 1992;Mariac et al 2006;Manning 2011), cultivated pearl millet displays tremendous phenotypic variability for traits such as flowering time, panicle length, grain and stover characteristics, tolerance to drought, pests and diseases, as well as nutritional value (Bhattacharjee et al 2007;Stich et al 2010;Bashir et al 2014aBashir et al , 2014bPucher et al 2014Pucher et al , 2015. This can be attributed to genetic differentiation as a consequence of many factors including local adaptation, selection and genetic drift, which can lead to non-random distribution of important agronomic traits (Hedrick 2005;Lewis 2010).…”
Section: Introductionmentioning
confidence: 99%